2004
DOI: 10.1080/14445921.2004.11104165
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pricing on Time-on-Market in High-Rise Multiple-Unit Residential Developments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 20 publications
5
27
1
2
Order By: Relevance
“…This is reflected in the positive and statistically significant coefficient on the indicator variable for HIGHRISE rather than the premium Wong et al (2011) found for low-rise buildings in Hong Kong. West-facing units sell for significantly less than units on the other sides of the building (similar to Li, 2004), while south-facing units garner the highest prices (similar to Shimizu et al (2010) and Choy et al (2012)). The west-facing units suffer from heat from the afternoon sun without the benefit of air conditioning.…”
Section: Resultsmentioning
confidence: 99%
“…This is reflected in the positive and statistically significant coefficient on the indicator variable for HIGHRISE rather than the premium Wong et al (2011) found for low-rise buildings in Hong Kong. West-facing units sell for significantly less than units on the other sides of the building (similar to Li, 2004), while south-facing units garner the highest prices (similar to Shimizu et al (2010) and Choy et al (2012)). The west-facing units suffer from heat from the afternoon sun without the benefit of air conditioning.…”
Section: Resultsmentioning
confidence: 99%
“…Because all the units in a building are offered to the market at the same time, the amount of internal competition varies over time. Li (2004) finds that the number of units in a phase or project is positively related to TOM.…”
Section: Theory and Previous Researchmentioning
confidence: 98%
“…Meanwhile, An, Cheng, Lin, and Liu (2013) assert that in a market where demand is strong and house values appreciate over time, longer TOM can lead to higher expected prices than in a stable market, encouraging a seller to hold out for a higher price. As for competition, Li (2004) finds that a higher market take up rate among competitors' presale units leads to longer TOM. Because all the units in a building are offered to the market at the same time, the amount of internal competition varies over time.…”
Section: Theory and Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely known that homebuyers, when searching for desired real property, increasingly rely on the Internet -as has been shown in numerous studies over the years (Littlefield J. E. et al, 2000;Seiler M. J. et al, 2012) Market (TOM) in relation to the listed price and pointed out toward diverse interaction effects that depend on housing markets (Cubbin J, 1974;Trippi R. R., 1977;Miller N. G., 1978;Ford J. S. et al, 2005;Li. W., 2004;McGreal S. et al, 2009).…”
Section: Introductionmentioning
confidence: 99%